2009 IEEE Symposium on Computational Intelligence and Games 2009
DOI: 10.1109/cig.2009.5286500
|View full text |Cite
|
Sign up to set email alerts
|

Player modeling using self-organization in Tomb Raider: Underworld

Abstract: Abstract-We present a study focused on constructing models of players for the major commercial title Tomb Raider: Underworld (TRU). Emergent self-organizing maps are trained on high-level playing behavior data obtained from 1365 players that completed the TRU game. The unsupervised learning approach utilized reveals four types of players which are analyzed within the context of the game. The proposed approach automates, in part, the traditional user and play testing procedures followed in the game industry sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
150
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(163 citation statements)
references
References 11 publications
0
150
0
3
Order By: Relevance
“…For example, Canossa et al [11] used self-organizing maps to identify player types among tens of thousands of players of the modern action-adventure game Tomb Raider: Underworld; in a follow-up study, Mahlmann et al [16] managed to predict future behavior of players, including at what level players stop playing the game, based only on early-game player behavior.…”
Section: Player Modeling and Game Data Miningmentioning
confidence: 99%
“…For example, Canossa et al [11] used self-organizing maps to identify player types among tens of thousands of players of the modern action-adventure game Tomb Raider: Underworld; in a follow-up study, Mahlmann et al [16] managed to predict future behavior of players, including at what level players stop playing the game, based only on early-game player behavior.…”
Section: Player Modeling and Game Data Miningmentioning
confidence: 99%
“…A study conducted by Drachen et al (2009) looked at how a set of players completed the popular adventure game Tomb Raider: Underworld. They identified four different styles each with different playing patterns and solutions to specific problems and also a certain level of performance.…”
Section: Behavioral Basismentioning
confidence: 99%
“…The performance of each model was described, and sets of 4-5 playstyles identified across each model. The authors concluded that Archetype Analysis (AA) [13], [12] performs best in terms of developing clearly separated and explainable profiles, the latter forming a key quality criteria in games-based behavioral profiling as argued by Drachen et al [10].…”
Section: Related Workmentioning
confidence: 99%
“…A substantial number of papers have been published on behavioral profiling in games. The first paper to specifically utilize behavioral profiling in commercial game titles was Drachen et al [10] who worked with Self-Organizing Networks. The majority of previous work is focused on employing cluster analysis or segmentation methods, but comparative analyses were provided by Bauckhage et al [11] and Drachen et al [12].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation